2019
DOI: 10.3390/pharmaceutics11100514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Size and Concentration of PLGA-PEG Nanoparticles on Activation and Aggregation of Washed Human Platelets

Abstract: Nanotechnology is being increasingly utilised in medicine as diagnostics and for drug delivery and targeting. The small size and high surface area of nanoparticles (NPs), desirable properties that allow them to cross biological barriers, also offer potential for interaction with other cells and blood constituents, presenting possible safety risks. While NPs investigated are predominantly based on the biodegradable, biocompatible, and FDA approved poly-lactide-co-glycolide (PLGA) polymers, pro-aggregatory and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This high heterodispersity of the 321 nm NPs may have resulted in the formation of a larger physical barrier to the passage of light through the sample during measurement, hence, giving a lower % PA for these NPs. The results observed in this study were similar to the platelet aggregometry data for thrombin-activated WPs incubated with various sized NPs which we reported previously [ 9 ]. The response of platelets in PRP in the presence of NPs did not appear to vary despite the additional components present in PRP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This high heterodispersity of the 321 nm NPs may have resulted in the formation of a larger physical barrier to the passage of light through the sample during measurement, hence, giving a lower % PA for these NPs. The results observed in this study were similar to the platelet aggregometry data for thrombin-activated WPs incubated with various sized NPs which we reported previously [ 9 ]. The response of platelets in PRP in the presence of NPs did not appear to vary despite the additional components present in PRP.…”
Section: Discussionsupporting
confidence: 92%
“…Using the formulation parameters as those used in our previous study, PLGA-PEG NPs of three different sizes similar to those previously reported, were obtained [ 9 ]. The average particle size (PS) and polydispersity index (PDI) obtained were 113 ± 7.22, 321 ± 46.43, and 585 ± 5.87 nm and 0.10 ± 0.03, 0.55 ± 0.07, and 0.67 ± 0.03 respectively, for PLGA-PEG concentrations of 10, 55, and 100 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PLGA toxicity was investigated by Bakhaidar et al [ 29 ]. Here, the researchers studied the impact of size-selected PLGA–PEG nanoparticles on platelet activation and aggregation.…”
mentioning
confidence: 99%